MiRNAs as common regulators of the transforming growth factor (TGF)-β pathway in the preeclamptic placenta and cadmium-treated trophoblasts: Links between the environment, the epigenome and preeclampsia. (December 2016) - Brooks, Samira A.; Martin, Elizabeth; Smeester, Lisa; Grace, Matthew R.; Boggess, Kim; Fry, Rebecca C.
Abstract: Preeclampsia (PE) is a pregnancy disorder characterized by high blood pressure and proteinuria that can cause adverse health effects in both mother and fetus. There is no current cure for PE other than delivery of the fetus/placenta. While the etiology is unknown, poor placentation due to aberrant signaling of growth and angiogenic factors has been postulated as a causal factor of PE. In addition, environmental contaminants, such as the metal cadmium (Cd), have been linked to placental toxicity and increased risk of developing PE. Here, we use a translational study design to investigate genomic and epigenomic alterations in both placentas and placental trophoblasts, focused on the angiogenesis-associated transforming growth factor-beta (TGF-β) pathway. Genes within the TGF-β pathway displayed increased expression in both the preeclamptic placenta and Cd-treated trophoblasts. In addition, miRNAs that target the TGF-β pathway were also significantly altered within the preeclamptic placenta and Cd-treated trophoblasts. Integrative analysis resulted in the identification of a subset of Cd-responsive miRNAs, including miR-26a and miR-155, common to preeclamptic placentas and Cd-treated trophoblasts. These miRNAs have previously been linked to PE and are predicted to regulate members of the TGF-β pathway. Results from this study provide future targets for PE treatment.